SANTET BANYUWANGI: THE STRUGGLE BETWEEN STIGMA AND CULTURE POST-REFORMATION 1998: Santet Banyuwangi: Pertarungan Antara Stigma dan Budaya Pasca-Reformasi 1998 - Muhammad Agung Pramono Putro; Guruh Prasetyo; Jefri Rieski Triyanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The violence directed against alleged practitioners of witchcraft (santet) in Banyuwangi in 1998 resulted in a significant loss of life and left a lasting stigma on santet, which had long been embedded in the everyday cultural practices of the Osing community. This incident transformed the meaning of santet and contributed to its use as a subject of ridicule toward the Osing people of Banyuwangi. This study aims to examine Banyuwangi santet as an arena of contestation between social stigma and local cultural roots. Employing the historical method and drawing upon a socio-cultural methodological framework, this research reconstructs santet both as an element of intangible cultural heritage and as a historical phenomenon associated with the witchcraft and “ninja” violence that emerged in Banyuwangi during the post-Reformasi period. The findings indicate that the santet issue originated from a complex horizontal conflict that generated widespread social unrest at the grassroots level and later evolved into a vertical conflict characterized by allegations that the perpetrators of the violence were hired assassins referred to as “ninjas.” The novelty of this study lies in its analysis of these dynamics while simultaneously contributing recommendations for culturally based reconciliation and trauma recovery as preventive measures against the recurrence of similar incidents in communities that remain vulnerable to rumors and cultural violence. Furthermore, the study demonstrates that the unresolved legal status of this tragedy illustrates how stigma can reinforce collective violence, while the culture of santet itself is often misunderstood despite representing a complex form of local cultural heritage and wisdom.